Ironmaking and Steelmaking Processes Greenhouse Emissions, Control, and Reduction - Cavaliere, Pasquale (Springer International Publishing : Imprint: Springer, 2016)
This book describes improvements in the iron and steel making process in the past few decades. It also presents new and improved solutions to producing high quality products with low greenhouse emissions. In addition, it examines legislative regulations regarding greenhouse emissions all around the world and how to control these dangerous emissions in iron and steel making plants. .